Remoção dos íons Cr3+ utilizando a cinza da casca de arroz como adsorvente - Pereira, Fábio (Universidade Federal Rural do Semi-Árido, 2020)
There is great concern about the proper destination of industrial waste and this has motivated the development of technologies for the use of this waste. In relation to industrial effluents, adsorption has stood out as an effective technology for removing heavy metals. Nonconventional and low-cost adsorbents have been studied to replace activated carbon, which is the most widely used adsorbent in industries. In this work, rice husk ash (RHA), a residue from the calcination of rice husk, was characterized with the objective of using it as a trivalent chromium ion adsorbent. The ashes were characterized by X-ray diffraction, X-ray fluorescence and scanning electron microscopy. The chemical composition and morphology of the ashes were suitable for adsorption experiments. The adsorption tests of Cr3 + ions by the finite bath method were performed at pH 5.5. The ion concentration was determined using atomic absorption spectroscopy. Qualitative analysis of adsorption was also performed by absorption spectroscopy in the visible region by UV. The results revealed the removal with an efficiency of 73% at equilibrium time of 90 min.
Cr3 + ion removal using rice husk ash as adsorbent
Artigo
Keywords: Cinza da casca de arroz; Adsorção; Banho finito; Cromo; Rice husk ash; Adsorption; Batch; Chrome; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA